2017
DOI: 10.1136/bjophthalmol-2017-310157
|View full text |Cite
|
Sign up to set email alerts
|

Distinct clinical characteristics of atypical optic neuritis with seronegative aquaporin-4 antibody among Chinese patients

Abstract: Atypical ON with seronegative AQP4-Ab had unique clinical features in this Chinese cohort, including male predominance, an older age of onset, worse visual acuity recovery and resistance to corticosteroid therapy. This condition may be a distinct nosological entity with an unusual clinical and therapeutic profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
(15 reference statements)
0
4
1
Order By: Relevance
“…We found only one male patient in the NMOSD group and no male patient in the MS group. These findings are different from other studies; the female:male ratio was 3:1-10.7:1 in the NMOSD group and 1.5:1-5.9:1 in the MS group [ 28 - 32 ], which is lower than the results of our study. Simultaneous bilateral involvement was found in 29.3% in the NMOSD group, 26.1% in the MS group and 21.7% in the idiopathic group which were not statistically significantly different among three groups.…”
Section: Discussioncontrasting
confidence: 99%
“…We found only one male patient in the NMOSD group and no male patient in the MS group. These findings are different from other studies; the female:male ratio was 3:1-10.7:1 in the NMOSD group and 1.5:1-5.9:1 in the MS group [ 28 - 32 ], which is lower than the results of our study. Simultaneous bilateral involvement was found in 29.3% in the NMOSD group, 26.1% in the MS group and 21.7% in the idiopathic group which were not statistically significantly different among three groups.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies showed female predominance in ON, especially in NMOSD-ON patients [8]. Our previous study [16] showed that atypical ON with seronegative AQP4-Ab and MOG-Ab had distinct clinical features which included a male predominance, low relapse rate, and worse visual prognosis, which highlighted the need to increase our understanding of sex-specific aspect of ON to better prognostic assessment and further insight into ON pathophysiology. We evaluated our cohort's Chinese male patients with antibody-seropositive ON (Ab-ON) and found 57.9% (44/76) of these patients were seropositive for MOG-Ab.…”
Section: Discussionmentioning
confidence: 98%
“…It has been identified that NMOSD is more likely to develop in Asia, whereas MS is more prevalent in western countries [ 7 ]. Previously, we reported a cohort of Chinese ON patients with atypical clinical features and poor recovery [ 8 ]. African-American patients were also found to have more severe vision loss and less vision recovery [ 9 ].…”
Section: Introductionmentioning
confidence: 99%